2006
DOI: 10.1002/lsm.20410
|View full text |Cite
|
Sign up to set email alerts
|

Detection of sentinel nodes by a novel red‐fluorescent dye, ATX‐S10Na (II), in an orthotopic xenograft rat model of human gastric carcinoma

Abstract: Background and Objective: We developed a new imaging system to detect sentinel nodes (SNs) using a novel fluorescent tracer, ATX-S10Na(II), and investigated its usefulness in an animal model. Study Design/Materials and Methods: Human gastric carcinoma cells were implanted orthotopically into nude rats. ATX-S10Na(II) was injected subserosally into the primary tumor lesion, and visualized by a fluorescence spectro-laparoscope. Presence of tumor cells in lymph nodes (LNs) was determined by RT-PCR specific for hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…7, however, ATX-S10Na (II) is incorporated rapidly into lymphatic tissues after subserosal injection into the primary tumor. Our study confirmed for the first time that ATX-S10Na (II) is taken up by local lymphatic tissues when it is subserosally injected into the primary tumor lesion (Koyama et al, 2007a). One possible explanation for the phenomenon is that the chemical structure of ATX-S10Na (II) is water-soluble, but not lipidsoluble (Matsumoto et al, 2003;Mori et al, 2000aMori et al, , 2000bNakajima et al, 1992Nakajima et al, , 1998.…”
Section: Rapid Incorporation Into Lymphatic Tissuessupporting
confidence: 72%
See 3 more Smart Citations
“…7, however, ATX-S10Na (II) is incorporated rapidly into lymphatic tissues after subserosal injection into the primary tumor. Our study confirmed for the first time that ATX-S10Na (II) is taken up by local lymphatic tissues when it is subserosally injected into the primary tumor lesion (Koyama et al, 2007a). One possible explanation for the phenomenon is that the chemical structure of ATX-S10Na (II) is water-soluble, but not lipidsoluble (Matsumoto et al, 2003;Mori et al, 2000aMori et al, , 2000bNakajima et al, 1992Nakajima et al, , 1998.…”
Section: Rapid Incorporation Into Lymphatic Tissuessupporting
confidence: 72%
“…No obvious toxicity was observed in rats that were injected locally with ATX-S10Na (II) at a dose of 1.3-2.5 mg/kg in our study (Koyama et al, 2007a). This dosage is much smaller than that of systemic administration given intravenously at a dose of 5-25 mg/kg, which caused little, if any, toxicity in vivo (Matsumoto et al, 2003;Mori et al, 2000a;Nakajima et al, 1992Nakajima et al, , 1998.…”
Section: Little Toxicity In Humanmentioning
confidence: 53%
See 2 more Smart Citations
“…39,41,43,50,56 All the studies were designed as prospective trials. Of these, 37 (80%) were prospective descriptive trials, whereas 9 (20%) intentionally planned to include comparative groups.…”
Section: General Resultsmentioning
confidence: 99%